Strategi Pengembangan Produk Olahan Ikan Lele (Clarias Sp) (Suatu Kasus Di Ukm Mae Shetie Dan Ukm Abon Ikan Lele Kota Cilegon - Alfarisi, Muhammad Naufal; Anggraeni, Dian; Sariyoga, Setiawan (JURNAL AGRIBISNIS TERPADU, 2018)
UKM Mae Shetie and UKM Abon Ikan Lele is a catfish abon processing business located in Citangkil and Pulomerak Subdistrict, Cilegon City. The purpose of this research is to know the characteristic overview of UKM Mae Shetie and Abon Ikan Lele, analyzing internal and external factors that faced in developing processed of catfish product in UKM Mae Shetie and Abon Ikan Lele, formulating alternative development strategy of processed product of catfish in UKM Mae Shetie and Abon Ikan Lele and recommend the strategic priority of alternative product development strategies that can be applied to the processed business of catfish UKM Mae Shetie and Abon Ikan Lele. The type of research conducted is survey research and the method used is descriptive quantitative method, the respondent technique used is by census. The analysis tools used are IFE matrix, EFE matrix, IE matrix, SWOT matrix and QSPM matrix. IFE and EFE matrices are used to analyze both internal and external factors of SMEs. Both of IE matrix from SMEs indicates the companys position is in V cell. An alternative formulation of product development strategy is made using SWOT matrix which yields six alternative strategies of UKM Mae Shetie and seven alternative strategies of UKM Abon Ikan Lele. Based on the QSPM matrix of both UKM obtained the priority of the main strategy, that is expanding the market distribution network to various souvenir centers and supermarkets.